2016
DOI: 10.5558/tfc2016-062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sand burial and overstory tree age on seedling establishment in coastal Pinus thunbergii forests in the northern Shandong Peninsula, China

Abstract: Coastal Pinus thunbergii (Japanese black pine) forests in the northern Shandong Peninsula of China recently experienced widespread natural regeneration failure. This study identifies critical factors that affect natural regeneration of P. thunbergii. Seeds from trees of various ages (13-32 years) were used to investigate the effects of age and burial depth in sand on germination and seedling establishment. Results show that seed density in 2-5 cm soil decreased with increased distance from the shoreline. Sand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Much research has been conducted on natural regeneration of the P. thunbergii protection forests. In particular, the effects of seed tree age and salt stress [7], water stress [8], and sand burial [9] on seed germination have been systematically studied. One of the important findings from these studies is that seed tree age played an important role in the seed germination of P. thunbergii.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much research has been conducted on natural regeneration of the P. thunbergii protection forests. In particular, the effects of seed tree age and salt stress [7], water stress [8], and sand burial [9] on seed germination have been systematically studied. One of the important findings from these studies is that seed tree age played an important role in the seed germination of P. thunbergii.…”
Section: Introductionmentioning
confidence: 99%
“…Baraloto et al [16] showed that seed size influenced performance within and among eight neotropical tree species. A short germination time can cause P. thunbergii seedlings to have a longer growth time and larger individuals, which is vital for seedling establishment in the natural environment [9]. Larger seeds have more nutrients, which can improve the germination and seedling tolerance of Caragana microphylla Lam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of lateral cypress seeds of different parent tree sizes, It was found that the germination rate and germination index of Platycladus orientalis seeds increased with the increase of parent tree size [21]. It was shown similar results for Pinus thunbergii seeds, which were related to the increase of nutrient accumulation in the parent tree [22]. For the spring flowering seeds of T. austromongolica, the germination rate, germination index, and vigor index were I>II>III, and the highest quality of seeds was found in the diameter class I.…”
Section: Effects Of Mother Tree Size and Salt Stress On Early Seedlin...mentioning
confidence: 94%
“…The bare land outside the shrub area is subjected to wind erosion, while the shrub area is frequently partially or completely buried by sand (Figure 5d). Some studies have shown that moderate burial improved seed germination, seedling survival and the growth of herbaceous plants, such as Psammochloa villosa [35], Leymus secalinus [15], as well as of desert shrubs, such as Nitraria sphaerocarpa and Haloxylon ammodendron [7], while others also found that seed germination of Eremosparton songoricum [14] and Pinus thunbergii [36] decreased after shallow partial burial treatment. We found that the seed germination and seedling biomass of Caragana reached the highest level at a sand burial depth of 1-2 cm.…”
Section: Sandy Habitats Facilitate Seed Germination and Seedling Grow...mentioning
confidence: 99%